Disorder of the Microbiota and Mucosal Immunity of the Genital Tract in Women of Reproductive Age with Different Clinical Courses of Acute Uncomplicated Pyelonephritis - Rudenko, A.V.; Romanenko, A.M.; Pasiechnikov, S.P.; Mitchenko, M.V.; Romashchenko, O.V.; Taradiy, N.M.; Руденко, А.В.; Романенко, А.М.; Пасєчніков, С.П.; Мітченко, М.В.; Ромащенко, О.В.; Тарадій, Н.M. (PH "Akademperiodyka" of the NAS of Ukraine, 2023)
The research deals with the study of immuno-microbiological parallels of the genital tract in women with acute uncomplicated pyelonephritis with concomitant chronic pelvic inflammatory diseases. In addition to etiotropic antibacterial therapy, correction of the mucosal immunity state of the genital tract is crucial for the treatment of the disease and prevention of its recurrence. The purpose of the work was to investigate the contamination and state of local immunity of the genital tract in women with acute uncomplicated pyelonephritis with different clinical courses. Methods. 246 women of reproductive age suffering from acute uncomplicated pyelonephritis were studied, divided into three variants of the disease clinical course: group 1 - mild (n=105), group 2 - moderate (n=90), and group 3 - severe (n=51) courses. The scrapings of the mucous membrane of the cervical canal and washings from the vagina were obtained before the start of antimicrobial therapy. Quantitative determination of pathogens was carried out by sowing the biological material on solid nutrient environment. Identification of detached bacteria was carried out according to Bergeys. Mollicutes (Ureaplasma spp., Mycoplasma hominis) were determined by the cultural-fermentative method using test systems and the polymerase chain reaction. Vaginal washings of 121 sick women were used for immunological studies. The levels of myeloperoxidase, lysozyme, human β-defensin-2, immunoglobulins M, A, G, secretory IgA, lactoferrin, C3-component of complement, secretory component, and tumor necrosis factor-α were determined. The reference group consisted of 23 clinically healthy women. The Statistica 12.0 program package for Windows was used, and a difference of p<0.05 was considered verifi able. Results. In the majority of patients with acute uncomplicated pyelonephritis (85.6% of cases), concomitant chronic pelvic inflammatory diseases (colpitis, salpingitis, underlying medical condition of cervix) were observed. Classical bacteria were more often detected in vaginal washings of patients of all groups, while mollicutes were detected in scrapings of the mucous membrane of the cervical canal, whereas the frequency of their detection increased with increase in the pyelonephritis severity. The analysis of indicators of local immunity determined disorders of mucosal immunity of the genital tract in the form of increased levels of myeloperoxidase, IgA, and IgG relative to reference values. The highest levels of lysozyme and myeloperoxidase were determined in patients with a severe course of acute uncomplicated pyelonephritis (by 5.3 and 3.6 times more, respectively), and the content of immunoglobulins A, M, and G in patients with a mild course of the disease (by 3.2, 3.1, and 4.0 times more, respectively). An increase in the level of tumor necrosis factor-α was detected in all patients, although no significant differences from controls were found in any group, but the highest median value was recorded in patients with severe pyelonephritis. In the group of patients with a severe clinical course, the lowest median was observed for β-defensin-2, which makes it impossible to inhibit the synthesis of TNF-α and, thus, supports the inflammatory process. Conclusions. It has been proven that in women with acute uncomplicated pyelonephritis, the severity of the course probably correlates with infection of the genital tract by mollicutes, mainly in association with classical bacteria and with level of mucosal immunity disorder. The obtained results of microbiological and immunological studies of biological material collected before the start of antibacterial therapy in patients with acute uncomplicated pyelonephritis proved the need for a mandatory examination by a gynecologist to ascertain concomitant chronic pelvic inflammatory diseases and establish infection with mollicutes to provide relevant etiotropic treatment. The above is the basis for adding the data regarding laboratory examination and treatment to the management protocols of patients with acute uncomplicated pyelonephritis.